2016
DOI: 10.1016/j.hpb.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Biliary architecture of livers exhibiting right-sided ligamentum teres: an indication for preoperative cholangiography prior to major hepatectomy

Abstract: ObjectiveTo obtain information about the basic biliary anatomy of livers with right-sided ligamentum teres (RSLT).Summary of background dataRSLT is a relatively rare anomaly with a reported incidence of 0.2–1.2%. Although the portal/hepatic venous and arterial anatomy of livers with RSLT has already been established, the biliary architecture of such livers remains unclear.MethodsRSLT was detected in 48 patients during 12,071 consecutive image readings (0.4%). Of these patients, the cholangiograms of 46 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…In the most common cases ( e.g ., an independent ramification of the right lateral portal pedicle), a surgeon’s misunderstanding and ligation of the left portal trunk result in a lack of portal flow in two-thirds of the whole liver during left hepatectomy[ 3 ]. Therefore, awareness of the type of anomaly is important before planning hepatectomy for patients with RSLT[ 1 , 3 , 4 ]. In 1997, Nagai et al[ 1 ] reported two types of portal vein classifications of RSLT, and later, Shindoh et al[ 3 ] and Nishitai et al[ 4 ] demonstrated the classification of arterial, portal, and biliary ramifications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the most common cases ( e.g ., an independent ramification of the right lateral portal pedicle), a surgeon’s misunderstanding and ligation of the left portal trunk result in a lack of portal flow in two-thirds of the whole liver during left hepatectomy[ 3 ]. Therefore, awareness of the type of anomaly is important before planning hepatectomy for patients with RSLT[ 1 , 3 , 4 ]. In 1997, Nagai et al[ 1 ] reported two types of portal vein classifications of RSLT, and later, Shindoh et al[ 3 ] and Nishitai et al[ 4 ] demonstrated the classification of arterial, portal, and biliary ramifications.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, awareness of the type of anomaly is important before planning hepatectomy for patients with RSLT[ 1 , 3 , 4 ]. In 1997, Nagai et al[ 1 ] reported two types of portal vein classifications of RSLT, and later, Shindoh et al[ 3 ] and Nishitai et al[ 4 ] demonstrated the classification of arterial, portal, and biliary ramifications. Portal ramification patterns were classified into three types: Independent right lateral, bifurcation, and trifurcation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2016, Nishitai et al [ 10 ] identified 4 intrahepatic biliary tree confluence patterns in their analysis of cholangiograms in 46 patients with RSLT. They found that the symmetrical type, in which the right hepatic duct drains Segment 6 + 7 plus the dorsal area of Segment 5 + 8 and the left hepatic duct drains the ventral area of Segment 5 + 8 and the left hemiliver, was the most frequent pattern.…”
Section: Discussionmentioning
confidence: 99%